2022
DOI: 10.15826/chimtech.2022.9.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment of multi-walled carbon nanotubes on the specific capacitance of supercapacitors

Abstract: To date, the research on carbon nanomaterials has progressed rapidly. More than 400 papers were written in 2021 on the application of carbon nanomaterials in various fields. The high demand for the use of such materials has increased due to a sharp increase in the demand for semiconductor materials and materials for supercapacitor electrodes and other electrical devices. Despite the unique physical properties of carbon nanomaterials, there are limitations to their use. To solve this problem, various methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…When comparing the specific capacitance of MWCNTs treated with sulfuric acid, which is one of the most frequently used oxidizers [ 44 ], it can be concluded that the treatment with dichromic acid leads to higher specific capacitance of material as well as lower C:O ratios [ 2 ]. Moreover, sometimes the oxidative treatment with sulfuric acid or nitric acid does not lead to a significant improvement in specific capacitance (the latter varied from 2.9 to 3.67 F g −1 for chemically treated CNT-based textile samples) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the specific capacitance of MWCNTs treated with sulfuric acid, which is one of the most frequently used oxidizers [ 44 ], it can be concluded that the treatment with dichromic acid leads to higher specific capacitance of material as well as lower C:O ratios [ 2 ]. Moreover, sometimes the oxidative treatment with sulfuric acid or nitric acid does not lead to a significant improvement in specific capacitance (the latter varied from 2.9 to 3.67 F g −1 for chemically treated CNT-based textile samples) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanomaterials have a wide range of applications in various fields and their research is cutting edge nowadays. The main prospective materials from this group are carbon nanotubes, which are interesting to be applied in supercapacitors [ 1 , 2 , 3 , 4 ], membranes [ 5 , 6 ], biosensors [ 7 ], polymer composites [ 8 , 9 ], batteries [ 10 ], gas sensors [ 11 , 12 , 13 ], etc. The creation of novel high-performance supercapacitors is on the way to large-scale production and extensive research should be carried out to overcome many problems towards this direction.…”
Section: Introductionmentioning
confidence: 99%